Digital Education Platform Berbasis Teknologi Untuk Meningkatkan Belajar Mahasiswa Dalam Software Engineering - Wardhani, Indah Kusuma (Universitas Multi Data Palembang, 2024)
This research aims to describe opportunities for students to improve their learning experience outside the classroom for Software Engineering learning by using educational platforms as technology-based learning media in the context of the digital era. It is known that currently the interest of students who are interested in Software Engineering material is increasing. For this reason, there needs to be innovation in learning, namely by implementing a learning platform, namely the Digital Education Platform. This learning platform is a problem solving process so that students become motivated and can improve their learning outcomes regarding Software Engineering material. This research shows that the web-based Digital Education Platform for student learning outcomes in Software Engineering learning can be a solution to the problems encountered in the student learning process in the current digital era. Learning using a web-based digital platform can enable student learning participation, especially in mastering Software Engineering material and can access it at home or anywhere. Thus, the Digital Education Platform can create an inclusive and technology-based learning environment which is very important to prepare students to face a future that is increasingly centered on technology.